Does intra-industry trade matter during economic crisis? An assessment of Malaysia-China trade - Yong, C.C.; Yew, S.Y.; Cheong, K.C.; Chin, M.Y. (Institute of China Studies, University of Malaya, 2015)
China is Malaysia’s largest trading partner. A significant part of this trade is intra-industry trade (IIT), Malaysia being a major participant in global supply chains that end in China, increasingly the final processing destination. Two economic crises in a decade have raised the question of the link between IIT and economic crises-specifically whether crises impact IIT or whether participation in IIT can protect against external risks, including from crises. This study finds that IIT between Malaysia and China has not been impacted by the Asian Financial Crisis but somewhat by the Global Financial Crisis. As a corollary, IIT has offered some protection from the former crisis but not from the latter. These findings have several implications. First, the severity of a crisis matters for IIT. Second, a strategy of participation in global supply chains ultimately depends on technological and organizational capability.